The ABCs of mental health at the university: a multi-level intervention design for promoting mental well-being - Nielsen, Line; Bermejo-Martins, Elena; Nelausen, Malene Kubstrup; Madsen, Cecilie Schacht; Riva, Elena; Koushede, Vibeke Jenny; Meilstrup, Charlotte Bjerre (Frontiers in Public Health, 2024)
Background: There is an escalating concern for the mental health of university students being recognized as a high-risk group for psychological distress. Despite research emphasizing the need to integrate mental well-being into higher education, existing interventions primarily focus on challenges and support services, leaving a gap in practical insights for promoting mental well-being at the university as a whole. Objectives: This paper aims to cover the theoretical and methodological foundations for the design and development of a complex multi-level intervention called the ABCs of mental health at the university (ABC-uni). Methods: Following the MRC framework for complex interventions, the design and development of a novel complex intervention is described (Phase I). Using the socio-ecological model and incorporating principles from health promotion charters, capacity building, organizational change models, and the principles of the ABCs of mental health a program theory for mental health promotion at the university is proposed. Following this theoretical foundation a logic model outlines the ABC-uni intervention components at structural, community, and individual levels. The components include staff training, campaign materials, a photovoice project, integration of mental well-being literacy into introductory programs, a credit-bearing course, and an online module. Preferably, most of these components are developed and carried out collaboratively with students at the university. As proposed in the logic model expected outcomes encompass heightened awareness, supportive environments, commitment, and accountability, aiming to enhance mental well-being across the entire university. The design and development of the intervention components occur at a Danish public university.. Discussion: This section addresses the strengths and limitations of the design of ABC-uni intervention.. Future research will cover the feasibility phase of each components of the ABC-uni intervention (phase II). The conceptual framework and program theory outlining mental health promotion at the university, along with the detailed description of the intervention components, provides valuable insights for fostering mental well-being in the university community.